Digital Technology Utilization for Increasing Rice Production in Farmer-Owned Enterprises: The Case of Lumpang Semar Sejahtera - Alfun Rachmat Hidayat; Siwi Gayatri; Tutik Dalmiyatun (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
This study examines the effects of internet accessibility and internet usage intensity on farmers’ knowledge and their implications for rice production at the Lumpang Semar Sejahtera Farmer-Owned Enterprise (FOE). The research is motivated by a production gap, where annual rice output (132 tons) remains significantly below consumer demand (240 tons). A quantitative approach was employed using a census method involving 70 rice farmers. Data were analyzed through path analysis with a bootstrapping technique to assess both direct and indirect relationships among variables. The findings reveal that internet accessibility does not significantly influence farmers’ knowledge but exerts a significant negative effect on rice production. In contrast, internet usage intensity has a positive and significant impact on both farmers’ knowledge and rice production. However, farmers’ knowledge does not mediate the relationship between internet-related variables and rice production. These results indicate that internet utilization has not yet functioned as an effective driver of productivity improvement through knowledge enhancement. Therefore, this study suggests that the FOE should prioritize increasing the intensity of internet use while integrating digital information into conventional farmer group activities to address existing structural constraints.